Ancient Greek Influence and Imagism In H.D's Early Poems - Djuhertati Imam Muhni (Humaniora, 1998)
In 1912 in the Museum-Street-Tea Shop Ezra Pound edited H.D's poem "Hermes of the Ways," signing it "H.D.lmagiste," and by this gesture the Imagist movement exists in the literary world. This often quoted information indicates that there is a significant influence of ancient Greek Literature On Imagist poets, particularly on H.D.; for example, one might note that the first two poems that appeared bearing the name Imagist, namely "Hermes of The Ways" and "Priapus" were based on Greek dedicatory epigrams. The purpose of the paper is to trace the ancient Greek influence on H.D.'s works, especially her purest Imagist poems. Though the discussion focuses on H.D.'s poetry, it also touches upon them works of two other Imagists, namely Ezra Pound's and Aldington's. These poets were two of the most important people in H.D.'s life as well as in her poetry. Pound came early in her life, and sparked her interest in Greek literature, while Aldington appeared in her London period,contributing a share in her intensive study of ancient Greek works. Accordingly, the paper falls into two main parts of discussion: first, on the personal and literary relationships between Ezra Pound, Aldington, and H.D. (Hilda Doolitle); second, the influence of Greek literature especially that of Sappho on H.D. as the main focus.